Peningkatan Pengetahuan tentang Diet Gout Arthirits melalui Pendidikan Kesehatan - Syenshie Virgini Wetik; Cyntia Theresia Lumintang (Jurnal Indah Sains dan Klinis, 2021)
The prevalence of gout arthritis is increasing due to the lack of information about the gout arthritis diet. This can be seen from the living habits of sufferers who do not understand the types of foods to avoid, consumption of foods with high purine levels, lack of exercise and rarely checking their health conditions at health facilities. The purpose of this study was to increase the patient's knowledge about the gout arthritis diet by using health education methods in the form of lectures. This research was carried out with a quasi-experimental research design with a one-group pretest and posttest approach on 30 gout arthritis patients in South Bongkudai Village, North Sulawesi. The sampling technique used was total sampling. The data collection instrument used a questionnaire related to age and gender as well as a questionnaire about dietary knowledge of gout arthritis. Data were analyzed through frequency distribution based on respondent characteristics and a chi-square test for bivariate analysis. The results showed that there was a significant increase in respondents' knowledge of 80% with the final result that there was an effect of providing health education on the level of patient knowledge about the gout arthritis diet with a p-value of 0.0196 (p < 0.05).